1998
DOI: 10.1159/000014029
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Apolipoprotein B Gene Expression in the Liver of Fetal Calves

Abstract: Changes in apolipoprotein (apo B) gene expression in the liver were determined in fetal calves from 90 to 260 days of intrauterine life. Results were compared with those obtained from the livers of 1-month-old calves and adult cows. By Western blot analysis using a rabbit antiserum to bovine apo B, apo B100 was detected from 90 days of intrauterine life. Apo B100 was shown to be the only form of apo B detected in the liver of fetal calves whatever the gestational age indicating the lack of editing process duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…Specific deletion of HNF4α in adult liver results in complete loss of ApoCIII expression [20]. Furthermore, the levels of ApoB and ApoCIII transcripts increase during development to reach the levels characteristic of adult liver [27]. Thus, the transcriptional responses that we have obtained using promoter studies recapitulate those observed during development: expression is lower during embryonic/fetal life when the less responsive HNF4α7 isoform is expressed.…”
Section: Resultssupporting
confidence: 93%
“…Specific deletion of HNF4α in adult liver results in complete loss of ApoCIII expression [20]. Furthermore, the levels of ApoB and ApoCIII transcripts increase during development to reach the levels characteristic of adult liver [27]. Thus, the transcriptional responses that we have obtained using promoter studies recapitulate those observed during development: expression is lower during embryonic/fetal life when the less responsive HNF4α7 isoform is expressed.…”
Section: Resultssupporting
confidence: 93%